The recursive thick frontier approach to estimating efficiency - Rien Wagenvoort; Paul Schure (European Investment Bank (EIB), 1999)
The traditional econometric techniques for frontier models, namely the Stochastic Frontier Approach (SFA), the Thick Frontier Approach (TFA) and the Distribution Free Approach (DFA) have in common that they depend on a priori assumptions that are, whether feasible or not, difficult to test. This paper introduces the Recursive Thick Frontier Approach (RTFA) to the estimation of technology parameters when panel data is available. Our approach is based on the assertion that if deviations from the frontier of X-efficient companies are completely random then one must observe for this group of firms that the probability of being located either above or below the frontier is equal to one half. This hypothesis can be tested for panel data sets but requires sorting of the full sample into a group of X-inefficient firms and a group of X-efficient (best practice) firms. The cost frontier is estimated using only the observations of the latter category.
Keywords: C13; C23; C40; 330; Cost/Production Function; Thick Frontier Approach; X-efficiency